Hubungan antara Love of Money, Machiavellian dengan Persepsi Etis: Analisis Berdasarkan Perspektif Gender - R. Rindayanti; Dekeng Setyo Budiarto (Akuntabilitas, 2017)
Ethical behavior is important since help educators and researchers understand future managers and executives’ ethical behavior in organization. The research investigates the relationship between gender, love of money, machiavellian and ethic behavior. Data collected  from 102 student of departemen of accounting. Result of the whole sample revealed that Machiavellian has significant effect on ethic behavior and there’s different perception on ethic behavior based from gender.